Pediatrics hyperuricemia in clinical practice: A retrospective analysis in 1753 children and adolescents with hyperuricemia - Stiburkova, Blanka; Lukesova, Marketa; Zeman, Jiri (Joint bone spine, 2025)
OBJECTIVES: Serum levels of uric acid (S-UA) are influenced by the interaction of genetic and environmental factors; detailed studies of hyperuricemia in children are rare. This retrospective study aimed to analyze the causes, risk factors, and therapeutic approaches associated with the development of hyperuricemia in childhood. METHODS: In a single-center study, serum uric acid levels were analyzed in 33,900 samples from 13,890 children and adolescents<19 years (6760 girls and 7130 boys) obtained between 2013 and 2023. Hyperuricemia was defined as S-UA>370μmol/L (6.22mg/dL) in girls and>420μmol/L (7.06mg/dL) in boys; mild hyperuricemia was defined as 370-420μmol/L in boys<13 years. RESULTS: In the analyzed group, hyperuricemia was found in 1753 patients (12.6%), including 586 girls and 864 boys; mild hyperuricemia was found in 303 boys<13 years. The most common associated conditions were obesity with body mass index>95th percentile (27.8% of girls, 26.3% of boys) and chronic kidney disease (18.6% of boys, 11.4% of girls). Hyperuricemia was also relatively common in children with connective tissue disorders (10.6%) or different inherited metabolic disorders (10.7%). Transitory hyperuricemia was found in 19.1% of girls and 10.1% of boys with acute gastroenteritis. Urate-lowering therapy was used in 73 children and adolescents with severe hyperuricemia (S-UA 556±107μmol/L, fraction excretion of UA 3.27±1.98%). Eight treated children had chronic kidney disease, nine were extremely obese, one had combined antiepileptic therapy, and 55 had inherited metabolic diseases, including 26 children with disorders of purine metabolism. The initial daily dose of allopurinol (50-100mg) normalized the S-UA (350±80μmol/L) in a majority of children, except for extremely obese adolescents (weight 98-149kg) where the dose had to be increased to 200-300mg. CONCLUSIONS: Asymptomatic hyperuricemia is a relatively common biochemical finding in pediatric clinical practice. The etiology of hyperuricemia should be carefully analyzed, and the value of individualized hyperuricemia management and the eventual benefits of urate-lowering therapy in children must be carefully considered.
Keywords: Male; Hyperuricemia; kyselina močová; retrospektivní studie; Child, Preschool; Risk Factors; Adolescent; Infant; Child; dítě; mužské pohlaví; Uric Acid; Severity of Illness Index; mladiství; předškolní dítě; lidé; ženské pohlaví; Humans; kojenec; rizikové faktory; stupeň závažnosti nemoci; Retrospective Studies; Female; hyperurikemie